2017
DOI: 10.1088/0031-8949/2017/t170/014005
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of powder metallurgically produced discontinuous tungsten fiber reinforced tungsten composites

Abstract: In future fusion reactors, tungsten is the prime candidate material for the plasma facing components. Nevertheless, tungsten is prone to develop cracks due to its intrinsic brittleness-a major concern under the extreme conditions of fusion environment. To overcome this drawback, tungsten fiber reinforced tungsten (W f /W) composites are being developed. These composite materials rely on an extrinsic toughing principle, similar to those in ceramic matrix composite, using internal energy dissipation mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 30 publications
9
40
0
Order By: Relevance
“…From Figure 7, it can be seen that, for Wf/W material, the force-displacement curves measured by the quantitative 3-point bending system give the same trend as the qualitative 3-point bending results in previous studies [5,7]: after an increasing linear-elastic response, the slope of the load deflection curve changes slightly; then the load further increases with several small load drops;…”
Section: Fracture Behavior Observationsupporting
confidence: 72%
“…From Figure 7, it can be seen that, for Wf/W material, the force-displacement curves measured by the quantitative 3-point bending system give the same trend as the qualitative 3-point bending results in previous studies [5,7]: after an increasing linear-elastic response, the slope of the load deflection curve changes slightly; then the load further increases with several small load drops;…”
Section: Fracture Behavior Observationsupporting
confidence: 72%
“…Various methods of building and constructing W f /W composites, either via Chemical Vapor Deposition (CVD) [38,39] or powder metallurgical (PM) processes [40,41] are available. Based on the work presented here and previous work [40,42,43,44,45,36,46], the basic proof of principle for CVD & PM-W f /W has been achieved. One of the crucial issues is to maintain as much of the properties of the constituents even after exposing the material to the production cycle and the fusion environment allowing for optimal extrinsic toughening and pseudo-ductile behaviour.…”
Section: Tungsten-fibre Reinforced Tungstenmentioning
confidence: 83%
“…With respect to the constituent properties it can be expected that when using doped W-wires they will retain their ductility even at elevated temperatures (above 1500 K) [42] and all mechanisms necessary for pseudo-ductility will be enabled [14,43,45]. Properties of the fibres can however be degraded by various circumstances e.g.…”
Section: Tungsten-fibre Reinforced Tungstenmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation is mitigated by using tungsten fibre-reinforced tungsten composites (W f /W) [7,8,9] which utilizes extrinsic mechanisms to improve the toughness similar to ceramic fibre-reinforced ceramics [10]. W fibres made of commercially available W wire (OSRAM GmbH) are used as reinforcements [11,12,13,14] in combination with a tungsten matrix produced either by a chemical deposition [7,15] or by a powder metallurgical process [16,17]. It has been shown that this idea in principle works in as-fabricated state [7,18] as well as after embrittlement [19,20].…”
Section: Introductionmentioning
confidence: 99%